Halothane and sevoflurane exert different degrees of inhibition on carotid body glomus cell intracellular Ca2+ response to hypoxia. - Pandit, J; Buckler, K (2010)
The purpose of this study was to ascertain if effects of halothane and sevoflurane (0.18-1.45 MAC) on the magnitude of the rise in intracellular calcium ([Ca(2+)]i with approximately 90s hypoxia (measured using indo-1 dye) in rat pup carotid body type I glomus cells. paralleled their known effects on the human hypoxic ventilatory response, where halothane is more depressive. We also assessed these agents' effect on [Ca(2+)]i response to 100 mM K(+). Halothane depressed the [Ca(2+])i transient in hypoxia more than sevoflurane (p = 0.036). Both agents also depressed the [Ca(2+)]i response to K+ - halothane more than sevoflurane (p = 0.004). These actions reflect their known influence on human hypoxic ventilatory response, consistent with the notion that the cellular process underlies the whole-body effect. The responses to K(+), which depolarises the cell membrane, indicates that in addition to a putative effect on K(+) channels, voltage-activated Ca(2+) channels may also be involved in the anaesthetic effect.